1989
DOI: 10.1152/ajpheart.1989.257.5.h1327
|View full text |Cite
|
Sign up to set email alerts
|

Contraction of diabetic rabbit aorta caused by endothelium-derived PGH2-TxA2

Abstract: Endothelium-dependent relaxations and vasoactive prostanoid production caused by acetylcholine were determined in the aortas of rabbits with diabetes mellitus induced by alloxan. Aortas of diabetic rabbits, contracted submaximally by phenylephrine, showed significantly decreased endothelium-dependent relaxations induced by acetylcholine compared with the aortas of normal rabbits. Indomethacin, a cyclooxygenase inhibitor, and SQ 29548, a prostaglandin H2-thromboxane A2 (PGH2-TxA2) receptor antagonist, normalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
165
4
9

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(188 citation statements)
references
References 0 publications
10
165
4
9
Order By: Relevance
“…These studies and our results contrast with observations that an overproduction of endothelium-derived vasoconstrictors, such as prostanoids, accounts for the impaired endothelium-dependent relaxations in diabetic blood vessels [12,13]. The existence of such an action of vasoconstrictor prostanoids in the kidney is not supported by our study, inasmuch as cyclooxygenase-inhibition did not restore the blunted relaxations observed in the diabetic animals.…”
Section: Basalcontrasting
confidence: 99%
See 1 more Smart Citation
“…These studies and our results contrast with observations that an overproduction of endothelium-derived vasoconstrictors, such as prostanoids, accounts for the impaired endothelium-dependent relaxations in diabetic blood vessels [12,13]. The existence of such an action of vasoconstrictor prostanoids in the kidney is not supported by our study, inasmuch as cyclooxygenase-inhibition did not restore the blunted relaxations observed in the diabetic animals.…”
Section: Basalcontrasting
confidence: 99%
“…The majority of the studies were done in large conduit arteries such as the aorta and the endothelial dysfunction was generally attributed to a reduced production or increased inactivation of NO [7±11] or to an overproduction of endothelium-derived vasoconstrictors, opposing the effects of NO [12,13]. These studies have, however, limited relevance to the alterations in the microcirculation and in the local control of tissue perfusion occurring in diabetes.…”
mentioning
confidence: 99%
“…in pial arterioles of diabetic rats in vivo (Mayhan et al, 1991) and in diabetic isolated aorta (Shimizu et al, 1993;Tesfamariam et al, 1989). Similar mechanisms may play a role after in vitro exposure of rabbit aorta to high glucose concentrations (Tesfamariam et al, 1990).…”
Section: Mechanisms Of Impaired Endothelium-dependent Vasodilatation mentioning
confidence: 90%
“…These EDCFs are thought to be released together with the EDRFs and oppose their e ects on the smooth muscle cells. The impaired relaxations are restored by non-speci®c cyclo-oxygenase blockade and prostanoid TP receptor antagonists, but not by thromboxane A 2 synthase blockers, suggesting that the culprit is a prostaglandin endoperoxide (Tesfamariam et al, 1989;Mayhan et al, 1991;Shimizu et al, 1993). On the other hand, cyclooxygenase inhibition did not restore impaired endotheliumdependent relaxations in isolated mesenteric arteries (Taylor et al, 1992;Diederich et al, 1994;Fukao et al, 1997), in the isolated perfused heart and kidney Fulton et al, 1996) and in the renal microcirculation in vivo (De Vriese et al, 1999), indicating that vasoactive prostanoids do not play an important contributory role to the endothelial dysfunction in these vascular beds.…”
Section: Mechanisms Of Impaired Endothelium-dependent Vasodilatation mentioning
confidence: 97%
“…Several endothelium-generated vasoconstrictors are produced in abnormally high amounts in diabetes, the main one being endothelin-1 [25]. At the same time, impaired production of nitric oxide (a vasodilator) is observed in endothelial dysfunction [26].…”
Section: Discussionmentioning
confidence: 99%